A Distributed Weighted Cluster Based Routing Protocol for MANETs - Chauhan, Naveen; Awasthi, L. K.; Chand, Narottam; Chugh, Ankit (Computer Networks and Information Technologies, 2011)
MANETs or Mobile ad-hoc networks are a form of wireless networks which do not require a base station for providing network connectivity. Mobile ad-hoc networks have many characteristics which distinguish them from other wireless networks which makes routing in mobile ad-hoc networks a challenging task. Cluster based routing scheme is one of the routing schemes for MANETs in which various clusters of mobile nodes are formed with each cluster having its own clusterhead which are responsible for routing between clusters. In this project we have designed an implementation of Distributed Weighted Clustering Algorithm. This approach is based on combined weight metric that takes into account several system parameters like the node degree, transmission range, energy and mobility of the nodes. After implementation we have evaluated the performance of our cluster based routing scheme in various network situations.